Capitalismo de vigilância : a privacidade na sociedade da informação - Carvalho, Mariana Amaral (2019)
With the technological advancement of communications and the proliferation of data in the digital environment, the right to privacy goes through constant evolutionary adjustments to keep pace with the context in which we live. The data in the digital environment is a cluster of information used to create profiles that can categorize people, using artificial intelligence, so that this information is later marketed. Thus, a change of paradigm is observed, with the transition from financial capitalism to surveillance capitalism. Against the foregoing, new legislation is arising for the protection and processing of personal data, such as the European General Data Protection Regulation - GDPR in the international scope and the Law 13.709/2018, the New General Law of Brazilian Data Protection, at the national level. Monetization of personal data is a battle for human dignity in a constantly digitized economy based on the extraction of "intelligence" and "value" from social relationships. It is from this perspective that the relevance of privacy and the glimpse of its protection through the protection legislations are revealed, adding ways that maximize the private well-being of many to the detriment of the economic interest of the few. The purpose of this dissertation is to analyze whether vigilance capitalism, even with the current protection mechanisms, compromises the effective protection of individuals' privacy in the information society. In order to do so, it was observed whether such protection mechanisms, technical in form, would be enough to effect the protection of privacy in the information society against surveillance capitalism. As far as the methodology is concerned, bibliographical research was essentially used, based on doctrine and legislation (national and foreign) dealing with privacy, personal data protection and surveillance capitalism. The descriptive research technique was applied, and a multidisciplinary analysis of the theme was carried out, which could adequately interpret such social, legal and economic phenomenon in contemporaneity.